Alpenloopings in Heimatklänge : Jodeln als Globalisierungsbewegung zwischen Tradition und Experiment - Martin, Silke; Justus Liebig University Giessen (My University, 2012)
The subject of my contribution is the functioning and effect of yodeling as an experimental form of vocals and singing as presented in Stefan Schwieterts documentary Heimatklänge [Sounds of home] (CH/D 2007); a recursive figure that co-constitutes what is identified as home and forges a sense of identity. Yodeling enables two home »loops« of a special kind: first, the recursive calling-singing in the Swiss Alps, which returns to inside the body as a result of a specific geographic location and its echo, and second, a worldwide sounds network, which through the art of the three Swiss vocal artists Erika Stucky, Noldi Alder, and Christian Zehnder, forms an acoustic bridge from Switzerland via Mongolia to the USA. The essay follows the associative structure of the ilm, which describes a circular movement that seeks to locate the concept of home while alternating in sounds and images between region and global, own and alien, traditional and experimental. With its description of the hypothesis of the origin of yodeling the study begins with a musicological perspective; next, it present an in-depth film analysis of Heimatklänges presentation of yodeling; finally, it formulates a globalization hypothesis in the context of culture studies, which in conjunction with the film endeavours to rethink the relationship between mountain landscape and people.
Keywords: ddc:780